O PAPEL DE PAREDE AMARELO - Fagundes de Oliveira, Dileane (Linguagens & Cidadania, 2020)
GILMAN, Charlotte Perkins. O papel de parede amarelo. 3. Ed. Trad. Diogo Henriques. Rio de Janeiro: José Olympio, 2017. 112 p.